Carbohydrate metabolism in ‘Housui’ Japanese pear floral buds exposed to different temperatures during endodormancy - HORIKOSHI, Humberto Mitio; SEKOZAWA, Yoshihiko; SUGAYA, Sumiko (Revista Teste SPGG, 2016)
To elucidate the effects of temperature on carbohydrate metabolism under mild winter conditions, Japanese pear (Pyrus pyrifolia Nakai) shoots were exposed to temperatures of 0, 6 and 12 °C for 600 hours during endodormancy, and subsequent bud dormancy release and carbohydrate metabolism were examined. Lateral floral buds were collected after 0, 200, 400, and 600 hours under the treatments, and after the accumulation of 2000, 4000, 6000, and 8000 growing degree hours (GDH) under heat accumulation, for carbohydrate and enzyme activities analysis. The bud burst was earliest for the 12 °C treatment, followed by the 6 and 0 °C treatments. Sucrose concentration under heat accumulation decreased early in buds from the 12 °C treatment. The sorbitol and sucrose concentration in the buds increased under 0 °C during the endodormancy. In contrast, glucose and fructose concentrations tended to increase under heat accumulation. Sucrose synthase (SS) activity increased early under heat accumulation in buds from the 6 and 12 °C treatments, but in 0 °C buds it increased more slowly, from 2000 GDH onwards. Similarly, soluble acid invertase (AI) activity increased markedly in all treatments from the middle of the heat accumulation period. We therefore suggest that a temperature of 12 °C during endodormancy may advance bud burst as the result of earlier conversion of sucrose into hexoses.